2019
DOI: 10.3389/fpsyg.2019.00219
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Nervosa and a Lost Emotional Self: A Psychological Formulation of the Development, Maintenance, and Treatment of Anorexia Nervosa

Abstract: In this paper, we argue that Anorexia Nervosa (AN) can be explained as arising from a ‘lost sense of emotional self.’ We begin by briefly reviewing evidence accumulated to date supporting the consensus that a complex range of genetic, biological, psychological, and socio-environmental risk and maintenance factors contribute to the development and maintenance of AN. We consider how current interventions seek to tackle these factors in psychotherapy and potential limitations. We then propose our theory that many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 257 publications
(363 reference statements)
10
64
0
Order By: Relevance
“…In line with previous literature findings, our AN patients presented a lower mood baseline and a higher EMSs score compared with HCs (Damiano et al, ; Meehan, Loeb, Roberto, & Attia, ). This is consistent with previous literature that showed how AN patients present a specific temperamental, cognitive, and behavioural profile with a rigid approach to changes that can affect a mild, flexible mind state as well as their connection with feelings and emotions (Duffy et al, ; Kaye et al, ; Oldershaw, Startup, & Lavender, ; Steinglass & Foerde, ). The literature has already shown that the AN patients present lower self‐esteem, higher fear of negative evaluation, and higher social physical comparison than controls, which are feelings that can affect social relationships (Cardi et al, ; Duarte, Ferreira, & Pinto‐Gouveia, ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous literature findings, our AN patients presented a lower mood baseline and a higher EMSs score compared with HCs (Damiano et al, ; Meehan, Loeb, Roberto, & Attia, ). This is consistent with previous literature that showed how AN patients present a specific temperamental, cognitive, and behavioural profile with a rigid approach to changes that can affect a mild, flexible mind state as well as their connection with feelings and emotions (Duffy et al, ; Kaye et al, ; Oldershaw, Startup, & Lavender, ; Steinglass & Foerde, ). The literature has already shown that the AN patients present lower self‐esteem, higher fear of negative evaluation, and higher social physical comparison than controls, which are feelings that can affect social relationships (Cardi et al, ; Duarte, Ferreira, & Pinto‐Gouveia, ).…”
Section: Discussionsupporting
confidence: 92%
“…It may be that deviation from the processes underlying normal brain development might contribute to EDs. Similarly, in keeping with long-standing theorizing regarding connections between identity and EDs, divergence from normative identity development might also contribute to ED etiology (Bruch, 1981;Verschueren et al, 2017a;Oldershaw et al, 2019). Unraveling these connections has the potential to greatly enhance our understanding of EDs during EA.…”
Section: Limitationsmentioning
confidence: 69%
“…In AN samples, mixed findings from previous studies, including decreased reward-related activation in cingulostriatal circuitry in acAN [16] and increased activation in executive control regions in recAN [22], might be attributable to differences in study design, weight status, and analytic strategies [13]. Perhaps more important in relation to AN, which is often conceptualized as a disorder characterized by a fundamental deficit in self-regulation [28][29][30][31], intertemporal choices are inherently self-relevant [32] and DD is also commonly associated with activation changes in regions of the default mode network (DMN; including medial prefrontal cortex, posterior cingulate/precuneus, inferior parietal regions) [33] that are involved in self-reflection and prospection [34,35].…”
Section: Introductionmentioning
confidence: 96%